Thiazolopyridines Improve Adipocyte Function by Inhibiting 11 Beta-HSD1 Oxoreductase Activity - Thirumurugan Rathinasabapathy; Kimberly Marie Palatini Jackson; Yiwen Thor; Ayuba Sunday Buru; Debora Esposito; Xu Li; Mallikarjuna Rao Pichika; Ahmad Sazali Hamzah; Slavko Komarnytsky (Journal of Chemistry)
Background. Glucocorticoid excess has been linked to clinical observations associated with the pathophysiology of metabolic syndrome. The intracellular glucocorticoid levels are primarily modulated by 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) enzyme that is highly expressed in key metabolic tissues including fat, liver, and the central nervous system. Methods. In this study we synthesized a set of novel tetrahydrothiazolopyridine derivatives, TR-01–4, that specifically target 11β-HSD1 and studied their ability to interfere with the glucocorticoid and lipid metabolism in the 3T3-L1 adipocytes. Results. Based on the docking model and structure-activity relationships, tetrahydrothiazolopyridine derivatives TR-02 and TR-04 showed the highest potency against 11β-HSD1 by dose-dependently inhibiting conversion of cortisone to cortisol (IC50 values of 1.8 μM and 0.095 μM, resp.). Incubation of fat cells with 0.1–10 μM TR-01–4 significantly decreased cortisone-induced lipid accumulation in adipocytes and suppressed 11β-HSD1 mRNA expression. Observed reduction in adipocyte fat stores could be partially explained by decreased expression levels of adipogenic markers (PPAR-γ, aP2) and key enzymes of lipid metabolism, including fatty acid synthase (FAS), hormone sensitive lipase (HSL), and lipoprotein lipase (LPL). Conclusions. The tetrahydrothiazolopyridine moiety served as an active pharmacophore for inhibiting 11β-HSD1 and offered a novel therapeutic strategy to ameliorate metabolic alterations found in obesity and diabetes.